"Well it's like someone at the other end cares about you." A qualitative study exploring the views of users and providers of care of contact-based interventions following self-harm. - Cooper, J; Hunter, C; Owen-Smith, A; Gunnell, D; Donovan, J; Hawton, K; Kapur, N (2011)
OBJECTIVE: We investigated the views of service users and staff regarding contact-based interventions (e.g., letters, telephone calls or crisis cards) following self-harm. METHOD: Self-harm patients recently discharged from an emergency department were selected using purposive sampling (n=11). Clinical staff from relevant service areas and voluntary staff took part in a focus group and individual interviews (n=10). Interviews were transcribed and thematic analyses were conducted using methods of constant comparison to ensure that emergent themes remained grounded in the data. RESULTS: Most service users and staff participants identified the period of time directly after discharge as the time of greatest need. A contact-based intervention was viewed by service users as a gesture of caring, which counteracted feelings of loneliness. Delivery by mental health specialists was preferred, initially by phone, but letters were considered helpful later. The intervention should be both genuine in delivery and linked to current services. Potential barriers included means of accessing the service and threats to privacy. CONCLUSION: The findings suggest that an appropriate design for an intervention might be the provision of an information leaflet, telephone calls (soon after discharge), then letters (offering continuity of contact). Aspects of value and concern expressed by service users should be helpful to clinicians and service providers.